Ultrasound-assisted extraction for enhanced retention of physicochemical properties of garlic powder obtained by spray-drying - Poojitha, P.; Jolius, Gimbun; Afiqah, Yeop; Athmaselvi, K.A. (Open Science Publishers LLP Inc., 2020)
This work aims to produce garlic powder with the retention of physicochemical properties by using different methods. Garlic is extracted by an ultrasonic-assisted extraction technique to remove the undesired compounds. In this study, garlic powder is incurred through freeze-drying and spray-drying with maltodextrin as a carrier agent. To compare the efficiency of two drying techniques, garlic is dried without maltodextrin. This study is intended to find a technique to get garlic powder with the best quality. The physicochemical and microstructural properties of the garlic powder obtained were analyzed and compared. It was found that garlic powder spray-dried with maltodextrin has the highest retention of physicochemical properties compared to those treated with other techniques. Although freeze-dried and spray-dried powder developed without carrier agent could maintain the flavor and color, they failed to hold the structure and formed into clusters soon after they are exposed to air. Thus, the obtained results showed spray-drying with maltodextrin as the best drying technology for the maintenance of its physical and chemical properties.